JENIS-JENIS LUMUT (Bryophyta) DI HUTAN SEKUNDER DESA SEPANDAN KECAMATAN BATANG LUPAR KABUPATEN KAPUAS HULU - Azwad, Rifaldi; Tavita, Gusti Eva; Prayogo, Hari (Universitas Tanjungpura, 2020)
Moss is an important pioneer plant that acts as vegetation fillers on deforested land and helps to stabilize eroded soil surfaces. The secondary forest area, Sepandan village is a forest area that is dominated by trees and has a variety of flora and fauna. One of the flora or plants in the forest is various species of mosses. The purpose of this research was to identify species of moss in the Secondary Forest Area of Sepandan Village, Batang Lupar District, Kapuas Hulu Regency. The research was conducted by the survey method and made an observation plot. The observation plot played systematically, and this research was conducted at 3 different heights namely 100, 150 and 200 masl. The results of the research identified that there are 15 types of mosses from 15 families. The species found at this height is Treubia lacunose. Based on the calculation of the presence frequency can be seen that Treubia lacunose was the species most found at the study site with a frequency of 28.12%.Keyword: Identification, Moss, Secondary forest, Sepandan village.